Analysis Of Supporting And Inhibiting Factors For Tourism Communication Based On Islamic Education In Government Of Langkat Regency, North Sumatra Province - Indira Fatra Deni Peranginangin; Syukur Kholil; Hasan Sazali (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Sustainable Tourism for Development, Indonesia's tourism brand, promotes local cultural assets. The Langkat Regency Government will maintain and visit this community culture ceremony. Langkat's sweetened fruit halua is a culinary tour, part of Langkat Regency's Islamic education-based tourism. Langkat Regency needs measurable management to implement its tourist program, and all sectors of society, the government, and the community can work together for successful tourism.This research studied supporting and inhibiting factors of local-based tourism communication management in Langkat Regency, North Sumatra Province, from planning, organizing, executing, and supervising.This study began with basic observations of tourism development conducted by the Langkat district government. The informants in this study were the Head of the Tourism Sector at the Langkat Regency Tourism and Culture Office, the Head of the Langkat Regency Bappeda, Langkat Tourism Observers, Religious Leaders, and Langkat Regency Youth Leaders, in accordance with the research problem.pment guide.This study used unstructured observation. Unguided observations were made. Data analysis relates to the Miles and Huberman model, which is the act of compiling and processing data such that it may be easily read and comprehended. Data analysis can also be defined as the discovery of elements or sections containing smaller categories of study data. The collected data was subsequently evaluated utilizing qualitative data analysis.Islamic Education-Based Local Tourism Planning in Langkat based on analysis of field data shows that the local aspect is maximized by the Langkat Regency administration as development planning written in the vision and mission of Langkat Regency, the 2019-2024 Strategic Plan, the 2019-2024 Regional Medium Term Development Plan, the 2021 Langkat Local Government Work Plan, and Regional Tourism Development Master Plan no 5 2020 as a tourism development. The dominance of Muslim communities in Langkat Regency and in Indonesia, providing a great opportunity for the high number of visitors who come, then from multiethnic factors, Langkat Regency has a stock of cultural rituals that can be elevated as local potential, are factors supporting the realization of local tourism based on Islamic education. Furthermore, the geographical aspect is the state of Langkat Regency's natural potential, which is excellent for development into tourism sites such as seashores, rivers, and mountains.The impediment to growing Islamic Education-based local tourism is that some suitable areas for locally-based tourist destinations are still administered traditionally, resulting in a slow pace of tourism growth in some regions due to finance.The Langkat Regency Government is required to promote culture's multicultural potential as a local symbol by blending abstractive cultures with real tourist locations